Philip of Harvengt's Vita Augustini : the medieval premonstratensians and the patristic model - Neel, Carol (Analecta Praemonstratensia, 1995)
Keywords: 👤 philip of harvengt

Philip of Harvengt and Anselm of Havelberg: The Premonstratensian Vision of Time - Neel, Carol (Church History: Studies in Christianity and Culture, 1993)
Keywords: 👤 anselm of havelberg; 👤 philip of harvengt

Man‘s Restoration: Robert of Auxerre and the Writing of History in the Early Thirteenth Century - Neel, Carol (Traditio, 1988)
The historical work of the Premonstratensian canon Robert of Auxerre († 1211) was one of the most influential of medieval chronicles. Vincent of Beauvais († 1264) borrowed heavily from it in Speculum historiale, the final section of his great encyclopedia. The content of the Auxerre chronicle, extant in its independent version in relatively few manuscripts, thus contributed to an essential element in the textual foundation of later medieval education. The shape of Robert's narrative, however, differed from that of Vincent's treatment of history. The canon of Auxerre wrote in an old genre and for a traditional end. His was the kind of monastic chronicle that had for centuries affirmed for Benedictine and reform congregations their connection to venerable tradition, and traced for them the workings of providence in time. Vincent's work, on the other hand, set the record of human experience alongside compendia about the divine and natural worlds. It thus represented the historiographical fulfillment of the thirteenth century's ambition to systematize knowledge.
Publisher: Cambridge University Press
Keywords: 👤 robert of auxerre

Gospel Salad: Conversion among the Twelfth-Century Premonstratensians - Neel, Carol (Studies in Medieval and Renaissance History, 2010)
Keywords: 📚 premonstratensian (general)

The historical work of Burchard of Ursberg, VI: Burchard's life and his historiographical achievement - Neel, Carol Leigh (Analecta Praemonstratensia, 1985)
Keywords: 👤 burchard of ursberg

The historical work of Burchard of Ursberg, V: the historian, the emperor and the pope - Neel, Carol Leigh (Analecta Praemonstratensia, 1984)
Keywords: 👤 burchard of ursberg

The historical work of Burchard of Ursberg, IV: Burchard as historian - Neel, Carol Leigh (Analecta Praemonstratensia, 1983)
Keywords: 👤 burchard of ursberg

The historical work of Burchard of Ursberg - Neel, Carol Leigh (Cornell University, 1981)
Keywords: 👤 burchard of ursberg

The historical work of Burchard of Ursberg, I: the Ursberg Chronicon text - Neel, Carol Leigh (Analecta Praemonstratensia, 1982)
Keywords: 👤 burchard of ursberg

The historical work of Burchard of Ursberg, II: the Ursberg Chronicon and the Historia Welforum tradition - Neel, Carol Leigh (Analecta Praemonstratensia, 1982)
Keywords: 👤 burchard of ursberg

The historical work of Burchard of Ursberg, III: the historian and his sources - Neel, Carol Leigh (Analecta Praemonstratensia, 1983)
Keywords: 👤 burchard of ursberg

Philip of Harvengt and Anselm of Havelberg: the Premonstratensian vision of time - Neel, Carol Leigh (Church history, 1993)
Keywords: 👤 anselm of havelberg; 👤 philip of harvengt

Women Religious and Extraregulars: Premonstratensian Nuns and the Beguines - Neel, Carol (Les religieuses dans le cloître et dans le monde des origines à nos jours: Actes du deuxième colloque international du C.E.R.C.O.R., Poitiers, 29 septembre-2 octobre 1988, 1994)
Keywords: 📚 premonstratensian (general)

The Premonstratensian Project - Neel, Carol (A Companion to Medieval Rules and Customaries, 2020)
Keywords: ⚖️ chapters and statutes

Norbert and early Norbertine spirituality - Antry, Theodore J.; Neel, Carol (Paulist Press, 2007)
Keywords: 👤 norbert of xanten

Anticimenon: on the unity of the faith and the controversies with the Greeks - Anselm of Havelberg (Liturgical Press, 2010)
Keywords: 👤 anselm of havelberg